1990
DOI: 10.1038/sj.bdj.4807133
|View full text |Cite
|
Sign up to set email alerts
|

Failed conventional bridge work from general dental practice: clinical aspects and treatment needs of 142 cases

Abstract: The reasons for failure of 142 bridges in 130 patients from general dental practice seen at the Bristol Dental Hospital from 1981 to 1986 were assessed. Most patients were either self-referred or sent by a dentist who had not made the bridge. The mean age of the bridges at failure was 6.2 years. The main single reasons for failure were secondary caries or apical pathology, but many bridges failed as a result of factors related to design and structure. Bridges of porcelain fused to gold or gold faced with acryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 0 publications
1
41
0
1
Order By: Relevance
“…A poorer adaptation refers to a greater gap between the FDPs and the abutment, and is associated with a sharp decline in the FDPs life owing to the higher incidence of secondary caries resulting from the invasion of pathogens from saliva or food 7) . Previous studies regarding the adaptation of FDPs fabricated by the SLA method have thus far been very limited 5) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A poorer adaptation refers to a greater gap between the FDPs and the abutment, and is associated with a sharp decline in the FDPs life owing to the higher incidence of secondary caries resulting from the invasion of pathogens from saliva or food 7) . Previous studies regarding the adaptation of FDPs fabricated by the SLA method have thus far been very limited 5) .…”
Section: Discussionmentioning
confidence: 99%
“…These methods make the manufacture of FDPs using metallic materials such as alloys much easier; however, information regarding the quality of the resulting prosthesis is still limited. Although many factors influence the quality of FDPs, the most important is the gap between the prosthesis and tooth forms or tooth preparations [6][7][8] . A few authors have previously reported assessments of the gap in FDPs manufactured using the SLS method [9][10][11] ; however, similar reports on the gap of FDPs fabricated using the Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The length of the 19 studies ranged from 1 year to 20 years, with an average length of about 8 years. There were other studies 16,17,[36][37][38][39][40][41][42][43][44] containing data that were not included in this publication. One article 36 presented information about fixed partial dentures by calculating survival rates with the Kaplan-Meier method.…”
Section: Fixed Partial Denturesmentioning
confidence: 99%
“…Walton et al, 10 Foster, 41 and Valderhaug 23 came to similar conclusions, namely that the mean life span with caries as the reason for failure was between 8.4 and 12 years, while for loss of retention, the mean life span was between 4.5 and 9 years. In the present study, the mean life span with caries as the reason for failure was 10.9 years, while for loss of retention, the mean life span was 6.1 years.…”
Section: The International Journal Of Prosthodontics 264mentioning
confidence: 51%